Prevalence of Hypertension and Associated Factors among Residents Aged ≥18 Years in Ganzhou, China: A Cross-Sectional Study - Junwang Gu; Qi Wang; Wei Qiu; Fen Lin; Chunmei Wu; Ming Hao; Ping Wu (International Journal of Hypertension)
Background. Reliable epidemiologic data on the present burden of hypertension are needed in developing region-specific strategies since previous studies have suggested that China is lagging in risk factor management. Objective. The study aimed at exploring the prevalence of hypertension and its associated factors among adult residents in Ganzhou, China. Methodology. A multistage, stratified, and cluster random sampling method was used to conduct the cross-sectional survey. The study selected four county-level districts in Ganzhou City, China, as the investigation area. Permanent residents aged ≥18 years who have settled in the area for 6 months or more were selected. A total of 7430 residents were involved in the study. Univariate and multivariate logistic regression analysis was carried out to identify predictors of hypertension. Results. The prevalence of hypertension in Ganzhou was 28.5%, and the age-standardized prevalence of hypertension was 22.4%. Univariate logistic regression analysis revealed that multiple variables have a statistically significant effect on the prevalence of hypertension. The elderly (odds ratio [95% CI]: 2.791 [2.594–3.004]), men (1.805 [1.583–2.058]), lower educated (0.848 [0.805–0.893]), a family history of hypertension (4.575 [3.900–5.368]), higher body mass index (1.344 [1.215–1.488]), central obesity (1.532 [1.304–1.799]), and less vegetable intake (1.150 [1.023–1.294]) were the major risk factors for hypertension. Conclusion. Hypertension is a major public health problem in Ganzhou and requires much effort to reduce its prevalence. An effective multifaceted implementation strategy is highly desirable to combat the emerging burden of hypertension.